LABIRIN: MODEL PEMBELAJARAN LABELI, BICARAKAN, DAN RINGKAS - Nike Kusumawati (Center of Language and Cultural Studies, 2015)
This article is presenting teaching model for elementary school students in writing as an academic literacy. The model cimbines two available techniques: Quantum and Picture and Picture as the basis of presentation. Basically, the model is named as LABIRIN (give label, talk, and summarize, Labeli, Bicarakan, Ringkas) and is considered applicable to to teach explanation writing texts. The process of teaching starts from teacher presents the LABIRIN model to arouse students’ interest in the structure of texts and their explanation. Teacher then asks students to make label on the sequence of events in the texts, talk the contents with groups, and write down the messages and presents before the class.